Pengaruh Mata Pelajaran PKN Terhadap Pembentukan Karakter Kewarganegaraan Indonesia di Sekolah Dasar - Efrilia Nadifa; Hidayatul Rahmi; Adrias Adrias; Salmaini Safitri Syam (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Civic Education has an important role in shaping the character of students' citizenship by teaching the rights and obligations as citizens, and basic values ​​in the life of the nation and state. Many of them do not understand the meaning of Indonesian citizenship knowledge, which results in a sense of nationalism in students no longer caring for each other in the school environment or around it. The purpose of this study is to explore the extent to which Civic Education influences the formation of Indonesian citizenship character in elementary school students. The research used in compiling this article is a qualitative approach. Then for the method used is a literature study. The results of the study showed that the subject of Civic Education (PKn) has a significant influence in shaping the character of Indonesian citizenship in elementary school students. PKn contributes to instilling the main character values ​​and citizenship skills that support active and responsible participation in community life. The conclusion of this study shows that the subject of PKn plays an important role in shaping the character of citizenship in elementary school students, through PKn learning, students not only gain knowledge of citizenship, but also develop attitudes and skills that reflect values ​​as good citizens.